PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN DI PT. INDO-RAMA SYNTHETICS Tbk. DIVISI SPUN YARNS - Sarif Hidayat (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
This study aims to determine the impact of the integration of the management system ISO 9001: 2008 is used as a variable X1 on the quality of human resources, ISO 14001: 2004 is used as a variable X2 on the working environment, OHSAS 18001: 2007 is used as a variable X3 about the health and safety to the quality of human resources.This study uses explanatory research and hypothesis testing, with survey technique, distributing questionnaires with Likert scale. Sampling technique with probability sampling, are used slovin formula and obtained a sample of 94 respondents.Data analysis used descriptive analysis and inferential analysis, namely: (1) The validity and reliability, (2) Multiple Regression Analysis, (3) analysis of partial correlation coefficients, (4) Multiple Correlation Analysis, (5) The coefficient of determination, (4 ) Hypothesis Testing and partial test (t test) and a simultaneous test (F test). The test results and analysis as follows:1. There is a positive and significant effect between the competence of the quality of human resources with a positive correlation 0.522. competence contribution to the Quality of human resources amounted to 27.22%, with a thitung value of 5.87 with a significance ttable 1.986.2. There is a positive influence and significant between the working environment of the employees with positive correlation 0.597. Environmental work contribute to the quality of human resources of 35.6%, with a value of 7.14 thitung of the significance ttable of 1.986.3. There is a positive and significant influence between K3 to the Quality of human resources with a positive correlation for 0.451. The occupational safety and health contributes to quality of human resources is 20.3%, with a value of 4.85 with a significant thitung t ttable 1.986.4. The strong relationship between variables simultaneously X1, X2, and X3 to Y by 0.628, the contribution of all independent variables on the dependent variable simultaneously by 39.4%, Fhitung 19.5 with signifkansi Ftabel 1.39. Keywords: ISO 9001, ISO 14001, OHSAS & COMPETENCE